Competency-based management and work performance in a service provider company in Huanuco - Narvaez del Aguila, Miguel B. (2024)
Objective: To determine the relationship between competency-based management and job performance of the administrative staff at EPS Seda Huánuco S. A., as of 2023. Materials and Methods: This research is of an applied type, with a correlational level, using a non-experimental correlational design. The population and sample comprised the 57 employees of Seda Huánuco, to whom a survey technique was applied, using a questionnaire as the instrument. To determine the results and test the formulated hypotheses, descriptive statistics were applied for frequency tables and graphs, as well as inferential statistics, where the correlation index was interpreted. Results: The results showed that competency-based management is significantly related to job performance. This is inferred from the level of significance obtained in inferential analysis or hypothesis testing, which was p = 0,000 < 0,05, indicating that the relationship is significant. Additionally, a Spearman correlation coefficient of 0,875 was obtained, indicating that the relationship is positive and high, meaning that as better competency-based management practices are implemented, job performance also improves significantly. Conclusions: There is a high and significant positive relationship between competency-based management and job performance of the administrative staff at EPS Seda Huánuco as of 2023.